2013
DOI: 10.1124/dmd.112.049965
|View full text |Cite
|
Sign up to set email alerts
|

P-Glycoprotein Increases Portal Bioavailability of Loperamide in Mouse by Reducing First-Pass Intestinal Metabolism

Abstract: P-glycoprotein (P-gp) and CYP3A (cytochrome P450 3A, generally; Cyp3a, rodent enzyme) in the intestine can attenuate absorption of orally administered drugs. While some suggest that P-gp enhances intestinal metabolism by CYP3A/Cyp3a during absorption of a dual substrate, others suggest that P-gp reduces the metabolism in the intestine when substrates are at subsaturating concentrations. Hence, to elucidate the cellular mechanisms that can address these divergent reports, we studied intestinal absorption of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
32
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(35 citation statements)
references
References 42 publications
3
32
0
Order By: Relevance
“…Our recent studies provided support for this hypothesis (Dufek et al, 2013). Furthermore, it was shown that the effect of P-gp on intestinal first-pass metabolism was dose dependent, such that P-gp-mediated efflux caused the greatest increase in the F G at doses that produced intestinal concentrations near the apparent K m for Cyp3a-mediated metabolism (Dufek et al, 2013). This was the first report of P-gp in the intestinal epithelium contributing to an increase, instead of a decrease, in the F G of any drug.…”
Section: Introductionsupporting
confidence: 59%
See 3 more Smart Citations
“…Our recent studies provided support for this hypothesis (Dufek et al, 2013). Furthermore, it was shown that the effect of P-gp on intestinal first-pass metabolism was dose dependent, such that P-gp-mediated efflux caused the greatest increase in the F G at doses that produced intestinal concentrations near the apparent K m for Cyp3a-mediated metabolism (Dufek et al, 2013). This was the first report of P-gp in the intestinal epithelium contributing to an increase, instead of a decrease, in the F G of any drug.…”
Section: Introductionsupporting
confidence: 59%
“…Hence, the following hypothesis was tested: P-gp-mediated efflux should decrease intestinal first-pass metabolism of loperamide, thus increasing the absorption of intact loperamide into the portal circulation [i.e., gut bioavailability (F G )] and attenuating or reversing the negative impact of AP efflux of the drug. Our recent studies provided support for this hypothesis (Dufek et al, 2013). Furthermore, it was shown that the effect of P-gp on intestinal first-pass metabolism was dose dependent, such that P-gp-mediated efflux caused the greatest increase in the F G at doses that produced intestinal concentrations near the apparent K m for Cyp3a-mediated metabolism (Dufek et al, 2013).…”
Section: Introductionmentioning
confidence: 81%
See 2 more Smart Citations
“…Inhibition of P-gp would therefore decrease the total intestinal metabolism. On the other hand, when P-gp limits absorption in the proximal small intestine, the absorption is shifted to more distal, less catalytically efficient segments that contain lower amounts of CYP3A (Watkins, 1997;Dufek et al, 2013), thus P-gp inhibition will increase metabolism. In addition, Pang et al (2009) stated that efflux by P-gp limits metabolism due to the competition between CYP3A and P-gp within the cell and that their interplay is independent of the mean residence time of drug in the system.…”
Section: Discussionmentioning
confidence: 99%